Pengembangan Aplikasi Chat Multi Bahasa Berbasis NLP Translation API - Sugiharto, M Iqbal Novananda; Cahyono, Nuri (AI Society & STMIK Indonesia, 2022)
Interacting with others is an essential part of human life.. Sometimes users experience problems using chat applications, namely language differences when communicating with foreigners. Based on these problems, the author aims to build a chat application with a mobile-based automatic translator. In this application, the user can choose the language that will be used as needed. This application development uses the React Native framework for mobile applications and uses the NLP translation API for translators. This chat application automatically translates messages into the language used by the user. After doing some testing on the application, it can be concluded that it is according to the design and can make it easier for users to communicate with different languages